Wealth and antenatal care utilization in Nigeria: Policy implications (2017)
Antenatal care (ANC) utilization is lower in Nigeria than the African average. We investigated the relationship between wealth and utilization of ANC and also assessed other determinants associated with ANC utilization in Nigeria. Using data of the most recent births within 5 years prior to a 2012 nationally representative survey, we modeled predictors of ANC utilization. Respondents in the wealthiest quintile were over five times (aOR D 5.5 (95% CI: 4.2–7.2) more likely to adequately use ANC. The odds of ANC use were generally lower among the poor and the least educated women living in rural areas who need ANC the most.